Dissociation, Stressors, and Coping in Patients of Psychogenic Nonepileptic Seizures - Neena S Sawant (SAGE Publishing, 2021)
Background: Psychogenic nonepileptic seizures (PNES) commonly present both to neurologists and psychiatrists and include a wide range of psychopathology. In order to understand the demographics, dissociative experiences, stressful life events, abuse, and coping in these patients, this study was undertaken. Methods: This was a cross-sectional, observational study. A total of 71 patients of PNES, referred from neurology, were assessed on Dissociative Experience Scale (DES), Scale For Trauma and Abuse, Presumptive Stressful Life Events Scale (PSLES), and Ways of Coping Questionnaire to ascertain the dissociative experiences; the prevalence of trauma, abuse, and stressful life events, and the coping mechanisms. Results: Females predominated, with the duration of PNES up to 2 years. The mean ± SD total DES score was 38.14 ± 14.1, indicating high dissociation. On the PSLES, for the stressful life events in the last one year, the mean score was 98.28 ± 87.1. Marital and family conflicts and death were reported more. History of childhood or adult physical and sexual abuse was less reported. History of head trauma was present in 13 patients. Emotion-focused coping was used more than problem-solving strategies. Conclusions: Very few Indian studies have looked into these nuances. This study has helped in improving the understanding of the various risk factors of PNES and the coping strategies, and in sensitizing psychiatrists and neurologists to enquire into trauma and abuse of these patients.